Origem, tamanho, danificação mecânica e tratamento de sementes de soja na região das missões do Rio Grande do Sul - Horner, Matheus da Costa (2013)
The present wok had the objectives do determine, mechanical injury, size, origin of soybean seeds used by farmers on the Missoes region of Rio Grande do Sul State. For the study a drill box survey and a questionnaire were used. The sample size was determined based on the mechanical injury percentage being a maximum of 20%. 133 samples were taken to estimate with 95% probability. The evaluation were mechanical injury and small seed screen retention with the larger ones. Mechanical injury was done using the sodiun hypochloride method at 5%. For the small seed retention was used to replications of 100 seeds. For the seed origin, treatment and cultivars a questionnaire was used. Based on the results the following conclusion were obtained: 1- On the seed grading process more than 42% of the seed lots do present small seeds mixed; 2- More than 50% of the seed lots do present more than 14% mechanical injury; 3- There are cultivars that are more suceptable to mechanical injury; and 4- Larger seed tend to present higher percentage of mechanical injury.